Evaluation of the Impact of Noise Pollution on Students in Congested Area of Rawalpindi - Akhtar, Javeed; Anjum, Nomana; Iftikhar , Nazia (Nurture, 2013)
Noise pollution can be defined as any unwanted or offensive sound that unreasonably intrude into and disturb our daily lives. The environmental noise contributes to developmental learning, particularly in regard to speech, language and reading. Due to ongoing developments, insufficient infrastructure, increase in vehicles and absence of good learning place, the ideal conducive educational setting is disappeared. The noise in and around schools has lead to more widespread problem of children’s learning behavior because noise is not only hazardous to children’s mental abilities but to their overall well-being as well. The study is carried out to evaluate the impact of noise on students in a congested area of Rawalpindi with the main objective to investigate and assess negative impacts of noise on students and teachers to provide a better understanding of how and why sound affects on learning ability of students. Saidpur road had been selected being a densely populated and busy road, which runs parallel to Murree road at 0.5 kilometers distance apart and originate from Pandora Chowk to Banni Chowk with an approximate length of 6.0 kilometers. Four schools were selected as sample schools for the study on this road. A sample population of 100 students and 20 teachers were selected for the questionnaire survey by taking 25 students and 5 teachers from each school. Questionnaire was designed to gather students’ and teachers’ perception about the noise problem in their schools. The sound pressure levels were recorded with the help of sound level meter (A-Weighted) on the road, inside school compound and in the occupied classrooms. The results obtained from study are compared with World Health Organization Standards on noise levels for classroom. It is concluded that noise levels are higher than the recommended levels in all the schools and have serious impact on student learning.